2018
DOI: 10.1016/j.celrep.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 Innate Lymphoid Cells Attenuate Inflammatory Arthritis and Protect from Bone Destruction in Mice

Abstract: Group 2 innate lymphoid cells (ILC2s) were detected in the peripheral blood and the joints of rheumatoid arthritis (RA) patients, serum-induced arthritis (SIA), and collagen-induced arthritis (CIA) using flow cytometry. Circulating ILC2s were significantly increased in RA patients compared with healthy controls and inversely correlated with disease activity. Induction of arthritis in mice led to a fast increase in ILC2 number. To elucidate the role of ILC2 in arthritis, loss- and gain-of-function mouse models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…Accordingly, in vivo ILC2 accumulation by IL-25 overexpression strongly induced Ccl1 transcripts in WT mice. By contrast, ILC2-deficient Tie2 cre Rora fl/sg mice (Omata et al, 2018) did not display Ccl1 mRNA induction upon IL-25 treatment ( Fig. 4 D).…”
Section: Resultsmentioning
confidence: 91%
“…Accordingly, in vivo ILC2 accumulation by IL-25 overexpression strongly induced Ccl1 transcripts in WT mice. By contrast, ILC2-deficient Tie2 cre Rora fl/sg mice (Omata et al, 2018) did not display Ccl1 mRNA induction upon IL-25 treatment ( Fig. 4 D).…”
Section: Resultsmentioning
confidence: 91%
“…69 A more recent study demonstrated that artificially increasing ILC2s significantly attenuated experimental arthritis in an IL-4/13-dependent manner. 71 Clinical relevance was demonstrated in remitting rheumatoid arthritis patients who had high numbers of ILC2s and IL-9 + ILC2s in their joints and circulation that inversely correlated with disease severity. 69,71 In a mouse cecal and ligation puncture model, sepsis induced IL-33 release and subsequent expansion of IL-9-secreting ILC2 in the lung, which prevented lung endothelial cell pyroptosis by attenuating caspase-1 activation.…”
Section: Il-13mentioning
confidence: 99%
“…71 Clinical relevance was demonstrated in remitting rheumatoid arthritis patients who had high numbers of ILC2s and IL-9 + ILC2s in their joints and circulation that inversely correlated with disease severity. 69,71 In a mouse cecal and ligation puncture model, sepsis induced IL-33 release and subsequent expansion of IL-9-secreting ILC2 in the lung, which prevented lung endothelial cell pyroptosis by attenuating caspase-1 activation. 70 Autocrine production of IL-9 supports ILC2 responses that co-ordinate epithelial cell maintenance and lung homeostasis.…”
Section: Il-13mentioning
confidence: 99%
“…Furthermore, RANKL expression was detected on a fraction of the ILC1s suggesting a possible role of ILCs to directly contribute to inflammatory osteolysis (Kindstedt et al., ). However, considering that reduction of ILC2s in mice worsened serum‐induced arthritis and collagen‐induced arthritis, and that increasing ILC2 numbers in these models diminished arthritis, ILC2s have anti‐inflammatory functions (Omata et al., ). In line with these observations, ILC2s can support resolution of inflammation by targeting eosinophils and the activation of regulatory M2‐like macrophages (Molofsky et al., ).…”
Section: Preamblementioning
confidence: 99%